Evaluation in Organizations: A Systematic Approach to Enhancing Learning, Performance, and Change - Wes Martz (The Evaluation Center at Western Michigan University, 2006)
A review of the book Evaluation in Organizations: A Systematic Approach to Enhancing Learning, Performance, and Change by Darlene Russ-Eft & Hallie Preskill, published in 2001 by Basic Books.